PERAN HUMAN CAPITAL DALAM MENINGKATKAN KINERJA PERUSAHAAN PADA LEMBAGA PENGEMBANGAN PERBANKAN INDONESIA (LPPI) - Ahmad Asrorudin (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2020)
This study examines the effect of Individual Capability & Motivation, Leadership, The Organizational Climate, and Workgroup Effectiveness on Non-Financial Performance of Companies in the Indonesian Banking Development Institute (LPPI). The research method used is quantitative methods. Samples in the study were 90 respondents. Data collection techniques using a questionnaire. The analysis technique used is the validity test, reliability test, regression analysis. The results showed that partially the Individual Capability & Motivation variable, the Leadership variable did not have a significant effect on the Company's Non-Financial Performance at the Indonesian Banking Development Institute (LPPI). Whereas The Organizational Climate and Workgroup Effectiveness have a significant effect on the Company's Non-Financial Performance at the Indonesian Banking Development Institute (LPPI). Simultaneously, Individual Capability & Motivation, Leadership, The Organizational Climate, and Workgroup Effectiveness have a significant effect on the Company's Non-Financial Performance at the Indonesian Banking Development Institute (LPPI) with a positive coefficient direction.